Video Game Equipment Loss and Durability in a Circulating Academic Collection - Robson, Diane; Bryant, Sarah; Sassen, Catherine (Evidence Based Library and Information Practice, 2023)
Objective – This article reviewed twelve years of circulation data related to loss and damage of video game equipment, specifically consoles, game controllers, and gaming peripherals such as steering wheels, virtual reality headsets, and joysticks in an academic library collection.Methods – The authors analyzed data gathered from game equipment bibliographic and item records. Only data related to the console system, game controllers, and peripherals such as steering wheels, virtual reality headsets, and joysticks were evaluated for rate of circulation, loss, and damage. Cables and bags were not evaluated because the replacement cost for these items is negligible when considering long-term budgeting and maintenance of a game collection.Results – The majority of video game equipment can be circulated without unsustainable loss or damage. The library has been able to continue circulating video game equipment without undue replacement costs or loss of access for its patrons.Conclusion – Although equipment will occasionally break or be lost, libraries should not let this unduly affect consideration when starting a video game collection.